2018
DOI: 10.1186/s12944-018-0770-0
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid ethyl ester improves endothelial dysfunction in type 2 diabetic mice

Abstract: BackgroundEicosapentaenoic acid (EPA) is thought to have many beneficial effects, such as anti-atherosclerogenic and anti-inflammatory properties. However, few studies have reported its effects of endothelial dysfunction in diabetes and its direct effects on the aorta. Here, we investigated the effects of EPA treatment on impaired endothelium-dependent relaxation of the aorta in KKAy mice, a model of type 2 diabetes.MethodsMale KKAy mice were fed a high-fat (HF) diet for 8 weeks to induce diabetes, after which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Phenylephrine, an α -adrenergic receptor agonist stimulates Ca 2+ entry through voltage-gated and store-operated Ca 2+ channels and activates Ca 2+ sensitization pathways such as protein kinase-C (PKC) and Rho-kinase [ 36 ]. Activation of PKC increases the myofilament force sensitivity to cytosolic Ca 2+ concentration and myosin light-chain (MLC) phosphorylation and thereby maintains VSMC contraction with smaller increases in cytosolic Ca 2+ concentration [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phenylephrine, an α -adrenergic receptor agonist stimulates Ca 2+ entry through voltage-gated and store-operated Ca 2+ channels and activates Ca 2+ sensitization pathways such as protein kinase-C (PKC) and Rho-kinase [ 36 ]. Activation of PKC increases the myofilament force sensitivity to cytosolic Ca 2+ concentration and myosin light-chain (MLC) phosphorylation and thereby maintains VSMC contraction with smaller increases in cytosolic Ca 2+ concentration [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that n-3 polyunsaturated fatty acids (n-3 PUFAs) found in fish oil-especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)-can improve lipid metabolism and blood lipid profiles, prevent the progression of atherosclerosis, and reduce the incidence of cardiovascular diseases [7] as well as liver and plasma triglyceride levels [8]. We previously demonstrated that chronic oral administration of EPA prevented endothelial dysfunction in a mouse model of type 2 diabetes [9]. n-3 PUFAs have also been reported to have various anti-cancer effects in several types of malignancy in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Direct administration of EPA and other metabolites induced relaxation in the aorta ring isolated from C57BL/6J mice. The relaxation activity is reported by the authors as endothelium independent [64].…”
Section: Effect Of the Endothelium On The Vasodilation Induced By Isomentioning
confidence: 90%
“…The authors concluded that CYP450 (cytochrome P450) and IKCa (K+ and Na+ channel) receptors are related to the induction of vasodilation by EPA in the mesenteric artery, while IKCa could be implicated in the relaxation exerted by DHA in the aorta [30]. Takenouchi et al [64] studied the effect of EPA ethyl ester (EPA-E) supplementation in the diabetic KKAy (transcription factor kayak) mouse and nondiabetic C57BL/6 mouse (10 mg/day, 4 weeks). Interestingly, after treatment, aorta rings isolated from nondiabetic C57BL/6 mice fed EPA-E improved the vasodilation exerted by ACh.…”
Section: Effect Of the Endothelium On The Vasodilation Induced By Isomentioning
confidence: 99%